Alectinib Induces a Durable (>15 Months) Complete Response in an ALK‐Positive Non‐Small Cell Lung Cancer Patient Who Progressed on Crizotinib With Diffuse Leptomeningeal Carcinomatosis. (7th January 2015) - Ou, Sai‐Hong Ignatius; Sommers, Karen R.; Azada, Michele C.; Garon, Edward B.
Abstract : This report describes a patient with ALK ‐rearranged non‐small cell lung cancer who developed diffuse leptomeningeal carcinomatosis as the only "site" of progression after a prolonged response to crizotinib and who has been treated successfully with a second‐generation ALK inhibitor alone for >15 months.